Pengaruh Pupuk Kompos Limbah Sayur dan Pupuk Npk Tablet Terhadap Pertumbuhan dan Produksi Jagung Manis (Zea mays L. Var. saccharata Sturt) - Rendra q Rakasiwi; Edison Anom; Gulat ME Manurung (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
This research is purposed to find out the effect of Vegetable Waste Compost and NPK Tablets compost fertilizer against growth and production of Sweet Corn (Zea mays L. Var. saccharata Sturt). The experiment held in experimental field of Agriculture Faculty of Riau University began from June 2013 to September 2013, this experiment used group random program in factorial form. The first factor is Vegetable Waste fertilizer in three level of fertilizer, K1 = 94 g/crop (5 ton/ha) K2 = 187 g/crop (10 ton/ha) K3 = 281 g/crop (15 ton/ha). The second factor is NPK Tablets in three level of fertilizer, T1 = 2 tablets/crop T2 = 4 tablets/crop T3 = 6 tablets /crop. The observation parameters are the plantation growth rate (cm), the plantation net-weight (g) in 42 days, the appearance of male flower (HST), the appearance of female flower (HST), the weight per cob (g), and the production per 3m2. Giving vegetable waste compost affects in appearance of male and female flower but does not affect the plantation growth rate, the net-weight of plantation, the weight per cob and the production per plot. Giving NPK Tablets does not affect the plantation growth rate, the net-weight of plantation, the weight per cob and the production per plot. Keywords: growth, production, Vegetable Waste Compost fertilizer, NPK Tablets Compost fertilizer, sweet corn